2017
DOI: 10.1002/aenm.201701905
|View full text |Cite
|
Sign up to set email alerts
|

NiCoFe‐Layered Double Hydroxides/N‐Doped Graphene Oxide Array Colloid Composite as an Efficient Bifunctional Catalyst for Oxygen Electrocatalytic Reactions

Abstract: Ternary NiCoFe‐layered double hydroxide (NiCoIIIFe‐LDH) with Co3+ is grafted on nitrogen‐doped graphene oxide (N‐GO) by an in situ growth route. The array‐like colloid composite of NiCoIIIFe‐LDH/N‐GO is used as a bifunctional catalyst for both oxygen evolution/reduction reactions (OER/ORR). The NiCoIIIFe‐LDH/N‐GO array has a 3D open structure with less stacking of LDHs and an enlarged specific surface area. The hierarchical structure design and novel material chemistry endow high activity propelling O2 redox. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
161
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(168 citation statements)
references
References 51 publications
6
161
0
1
Order By: Relevance
“…As revealed in Figure b, the Co 2p of Ni 2 Co 1 Zn‐LDH exhibits two spin–orbit doublets of Co 2p 3/2 and Co 2p 1/2 that correspond to a low energy peak of 778.9 eV and a high energy peak of 797.6 eV, respectively. After vulcanization, the two peaks are shifted to lower binding energies of 781.0 eV (Co 2p 3/2 ) and 796.8 eV (Co 2p 1/2 ) (the spin‐energy separation changes from 15.3 to 15.8 eV), which implies the electron transfer from the S molecules to Co atoms and the density of the electron clouds from S increases, proving the Co 2+ /Co 3+ are maintained and reflecting the distinct chemical interaction between S and Co . Moreover, the XPS spectrum of O 1s has an obvious shift of 0.8 eV, demonstrating that the electronic structure of Ni 2 Co 1 Zn‐LDH has changed (Figure c) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As revealed in Figure b, the Co 2p of Ni 2 Co 1 Zn‐LDH exhibits two spin–orbit doublets of Co 2p 3/2 and Co 2p 1/2 that correspond to a low energy peak of 778.9 eV and a high energy peak of 797.6 eV, respectively. After vulcanization, the two peaks are shifted to lower binding energies of 781.0 eV (Co 2p 3/2 ) and 796.8 eV (Co 2p 1/2 ) (the spin‐energy separation changes from 15.3 to 15.8 eV), which implies the electron transfer from the S molecules to Co atoms and the density of the electron clouds from S increases, proving the Co 2+ /Co 3+ are maintained and reflecting the distinct chemical interaction between S and Co . Moreover, the XPS spectrum of O 1s has an obvious shift of 0.8 eV, demonstrating that the electronic structure of Ni 2 Co 1 Zn‐LDH has changed (Figure c) .…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, the corresponding XPS of Co and Ni are exhibited in Figure g,h, respectively. As the current densities increase from 1 to 10 A g −1 , a polarization reaction is inevitable because of that the extensive electrolyte ions will be adsorbed on the interface between electrode and electrolyte, which may destroy the equilibrium potential and change the surface electronic structure of the active materials, further leading to the decrease of binding energy and reflecting the change of valence state . Therefore, the analysis of Raman and XPS may reflect the possible mechanism that the electrochemical capacity of electrode materials decreases with the increase of current densities.…”
Section: Resultsmentioning
confidence: 99%
“…The HER and OER performances are supposed to be enhanced effectively via multiple advantages: 1) the heterostructure maximizes direct interfacial contact between 3d transition metal atoms and defects on carbon, remarkably enhancing electron transfer and shortening diffusion distance; 2) the DG with highly active defective sites offers extraordinary specific surface area and superior conductivity; and 3) the NiFe‐LDH nanosheets on DG possess good dispersion and superior structural integrity. Coincidentally, Pan et al reported an in situ synthetic route of defect‐induced nucleation for the preparation of NiCoFe‐LDH array on nitrogen‐doped graphene oxide (N‐GO) . Taking advantage of the synergistic effect between the two components, the hybrid NiCoFe‐LDH/N‐GO offered more accessible active sites and faster electron transport than the single counterpart, which promoted the bifunctional application for both OER and ORR.…”
Section: Controllable Synthesis Of Lmhsmentioning
confidence: 99%
“…[26] The O1sp eaks of electrocatalysts are mainly located at 530.90 eV ( Figure S6, Supporting Information), which are well indexedt ot he oxygen speciesi n phosphates. [28] The concentration of these two cobalt speciesa re listed in Table S3, Supporting Information. Upon deconvolution, the Co spectrac ould be divided into peaks of Co 2 + located at 781.20 eV,C o 3 + located at 780.12 eV,a nd Co satellitesa t 785.50 eV.…”
mentioning
confidence: 99%
“…Upon deconvolution, the Co spectrac ould be divided into peaks of Co 2 + located at 781.20 eV,C o 3 + located at 780.12 eV,a nd Co satellitesa t 785.50 eV. [28] On the other side, the Co 3 + can also facilitatet he surfaceo xygen adsorptionw ith an improved CoÀOb and strength, and, therefore, promote ORR kinetics. It is found that the concentration of Co 3 + increases with the creation of Na-ion defect until the presenceo ft he secondary phase.…”
mentioning
confidence: 99%